A Broad-Spectrum Monoclonal Antibody-Based Heterologous ic-ELISA for the Detection of Multiple Pyrethroids in Water, Milk, Celery, and Leek - Sulin Hou; Dandan Zhang; Zhenyu Xu; Yun Shen; Yulian Wang (Foods)
Pyrethroids are one of the most commonly used insecticides worldwide in agriculture, public health, and household products. To monitor the presence of pyrethroids in the environment and in food, a broad-spectrum monoclonal antibody (mAb), CL/CN-1D2, was prepared. This mAb demonstrates a 50% inhibitory concentration (IC50) for different pyrethroids: cypermethrin (129.1 µg/L), β-cypermethrin (199.6 µg/L), cyfluthrin (215.5 µg/L), fenpropathrin (220.3 µg/L), λ-cyhalothrin (226.9 µg/L), β-cyfluthrin (241.7 µg/L), deltamethrin (591.2 µg/L), and fenvalerate (763.1 µg/L). Using the mAb CL/CN-1D2, a highly sensitive heterologous indirect competitive ELISA (ic-ELISA) was developed for the rapid detection of these pyrethroids. The limit of detection (LOD) for the eight pyrethroids in water, milk, celery, and leek matrices ranged from 24.4 to 152.2 μg/kg. The recoveries ranged from 65.1% to 112.4%, with a coefficient of variation (CV) below 15%. A robust correlation (R2 = 0.9945) between the ic-ELISA and GC indicated that the ic-ELISA is a reliable tool for the rapid and cost-effective screening of pyrethroids residues.